Evaluating Arrowroot Starch Modification and Application in Wet Noodles - Puspitasari, Aprilia Bertha; Manuhara, Godras Jati; Fibri, Dwi Larasatie Nur; Muhammad, Dimas Rahadian Aji (Graduate School, Universitas Brawijaya, 2022)
Increasing the Resistant Starch (RS) level in food products containing naturally high starch content is important as RS has been acknowledged as a functional food ingredient. The purpose of this study is to determine the effect of steam-cooling treatment on the characteristic of arrowroot starch and to investigate the feasibility of arrowroot-based RS application on wet noodles. The study used a Completely Randomized Design (CRD) with one factor which was the steam-cooling cycle. Later, the substitution of 5%, 10%, and 20% of modified arrowroot starches on wet noodles was used, and then the consumer test was carried out. The results showed that the RS content of arrowroot starch remained after steam-cooling treatment. The treatment, however, reduced the water content and the brightness of the starch. Subsequently, arrowroot starch substitution without or with modification also reduced the lightness and tensile strength of wet noodles. Also, wet noodles with modified arrowroot starch substitution were significantly different in color, taste, and aroma parameters but were still acceptable to the panelists at a maximum substitution of 20%. The formulated wet noodles with modified arrowroot starch contained RS of 34.02% (d/b), and therefore they can be categorized as foodstuffs with high RS levels.